Peran Manajerial Dalam Pengelolaan Biaya Dan Kinerja Lingkungan Terhadap Kinerja Keuangan Dimoderasi Good Corporate Governance - Admi Hardianti; Adolf Z. D Siahay; Ulfah Rizky Muslimin (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2025)
This study aims to analyze the Managerial Role in Cost Management and Environmental Performance on Financial Performance, moderated by Good Corporate Governance. This study utilizes data from manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) in 2021-2024. This study uses a quantitative approach using secondary data. The sample selection uses purposive sampling. The number of companies used is 11 companies for 4 consecutive years, resulting in 44 samples. The analytical tool used in this study is Eviews 12 software. The results of this study indicate that Environmental Performance has a significant positive impact on Financial Performance, while Environmental Costs have no significant impact. Good Corporate Governance cannot moderate the effect of Environmental Performance and Environmental Costs on Financial Performance. This study emphasizes the importance of environmental management that goes beyond compliance, to increase the legitimacy and attractiveness of companies in the eyes of investors. This study provides insights for companies and stakeholders regarding the importance of sustainability.